Study on the effect of inflow conditions on wind flow acceleration in mountainous micro-topography. Issue 1 (1st June 2022) - Yin, Yuan; Li, Yangsen; Lin, Ruizong; Liu, Zhiwei; Fu, Benzhao; Huang, Guo; Zhang, Hongjie
Abstract: The acceleration of wind flow in mountainous areas can cause the destruction or collapse of transmission towers. The wind speed and direction of inflow have a significant impact on the flow acceleration in mountainous areas. The mountain terrain in the coastal area of Fujian was selected to study the influence of the inflow wind speed and direction on the acceleration effect. By analyzing the radar chart of the wind speed acceleration ratio of the monitoring points under 24 wind direction angles, the variation law of the wind speed acceleration ratio is consistent with the trend of the influence law obtained by the analysis of the surrounding terrain. The obtained simulation results are correct and credible, which can be used to correct the design wind speed of transmission lines in mountainous areas.